Radial-to-orbital motion transition in cylindrical Langmuir probes studied with particle-in-cell simulations. (10th December 2015) - Tejero-del-Caz, A; Fernández Palop, J I; Díaz-Cabrera, J M; Ballesteros, J
Abstract: A particle-in-cell (PIC) simulation of the plasma sheath around a cylindrical Langmuir probe has been developed to evaluate the ion current collected by the probe. The simulation includes the positive ion thermal motion and has been optimized by solely describing the positive ion motion. A transition from the prediction of the radial model to the orbital-motion-limited model is observed. The transition is explained as an effect of the positive ion thermal motion and the radial model is recovered when the positive ion to electron temperature ratio is decreased. The behaviour of this transition strongly depends on the dimensionless probe radius.